Improved bioavailability of buccal nanoemulsion vitamin D compared to conventional oral supplementation in patients with inflammatory bowel disease: a randomized controlled trial - Kojecký, Vladimír; Klhůfek, Josef; Kianička, Bohuslav; Kohout, Pavel (Frontiers in Medicine, 2025)
ObjectivesThe absorption of conventional cholecalciferol may be impaired in patients with inflammatory bowel disease (IBD). The bioavailability and optimal dosing of buccally absorbable nanoemulsion vitamin D in this population remain unclear. This study aimed to compare the effects of buccal nanoemulsion and conventional oral vitamin D supplementation on serum 25-hydroxyvitamin D (25OHD) levels in patients with IBD.MethodsThis was an open-label randomized trial. Patients with IBD were assigned to receive cholecalciferol in an oil emulsion at a dose of 14 000 IU weekly (GTTS) and orally absorbed cholecalciferol at dose 4000 IU twice a week (SPRAY) for 12–16 weeks during the winter months. Plasma 25OHD levels were measured at baseline and after the supplementation period.ResultsA total of 120 patients were analyzed. Among 75 subjects with CD and 45 with UC, 27% had active disease, and 24% of the Crohn’s disease patients had undergone ileocecal resection. The initial mean 25OHD level was 65.9 ± 21.0 nmol/l in the SPRAY group and 59.1 ± 27.7 nmol/l in the GTTS group. A similar increase of 9.3 ± 26.8 nmol/l (GTTS) and 9.2 ± 27.7 nmol/l (SPRAY) in 25OHD levels occurred in both groups, with similar variations. The proportion of subjects with normal and sub-normal levels following the substitution was comparable. The change in 25OHD level correlated negatively only with the baseline 25OHD level (p < 0.02) among all monitored variables.ConclusionIn IBD patients, the sufficient supplementation dose of the orally absorbable cholecalciferol is half that of the conventional oil emulsion (1143 IU/day vs. 2000 IU/day). Variable intestinal absorption is not a factor explaining inter-individual differences in 25OHD levels using a conventional vitamin D emulsion.